1999
DOI: 10.1177/009102609902800208
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Information Systems (HRIS): Providing Business with Rapid Data Access, Information Exchange and Strategic Advantage

Abstract: This article will review the major components of a Human Resource Information System (HRIS), including systems that are computerized and those that are not. These basic components provide a foundation for the reader to understand and explore how computerized and non-computerized information can assist human resources (HR) professionals achieve certain human resource objectives. There are many different types of computer software available to help in developing a comprehensive human resource information system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 0 publications
3
83
0
2
Order By: Relevance
“…Explanations for differences in the impact on HRIS on the strategic role played by HR have, on occasion, drawn on the wider IS literature, especially from the literature on ERP implementation. Thus, for example, there are a number of studies that have attributed the limited impact of HRIS on the strategic role played by HR to factors such as insufficient budget, lack of top management support, problems with user acceptance, lack of support for HR users, coordination problems and the impact of competing executive priorities (see Grant, Dery, Hall, Wailes, & Wiblen, 2009;Kovach & Cathcart, 1999). While these studies provide some important insights into a range of factors that can influence the impact of HRIS on HR, we argue that there is much to be gained from a deeper engagement with the growing body of IS literature that draws attention to mutually dependent relationship between organization and technology (Orlikowski & Scott, 2008).…”
Section: Towards An Actor-network Based View Of Hrismentioning
confidence: 99%
“…Explanations for differences in the impact on HRIS on the strategic role played by HR have, on occasion, drawn on the wider IS literature, especially from the literature on ERP implementation. Thus, for example, there are a number of studies that have attributed the limited impact of HRIS on the strategic role played by HR to factors such as insufficient budget, lack of top management support, problems with user acceptance, lack of support for HR users, coordination problems and the impact of competing executive priorities (see Grant, Dery, Hall, Wailes, & Wiblen, 2009;Kovach & Cathcart, 1999). While these studies provide some important insights into a range of factors that can influence the impact of HRIS on HR, we argue that there is much to be gained from a deeper engagement with the growing body of IS literature that draws attention to mutually dependent relationship between organization and technology (Orlikowski & Scott, 2008).…”
Section: Towards An Actor-network Based View Of Hrismentioning
confidence: 99%
“…The researchers found that most Hong Kong industries perceived quick response time and increased access to information to be the greatest benefits in implementing HRIS, while the greatest impediment was insufficient funding. These findings are supported by those of Kovach and Cathcart (1999), Beckers and Bsat (2002), and the Institute of Management and Administration (2002), who found that a comprehensive HRIS necessitates a large budget to implement and maintain. Ngai et al (2004) also found a statistically significant difference regarding certain potential advantages and barriers to implementation of HRIS between HRIS adopters and non-adopters, as well as between small, medium, and large organizations.…”
Section: Hris Applicationsmentioning
confidence: 55%
“…Tannenbaum (1990) defines HRIS as "a technology-based system used to acquire, store, manipulate, analyze, retrieve, and distribute pertinent information regarding an organization's human resources." Kovach et al (1999) define HRIS as a systematic procedure for "collecting, storing, maintaining, retrieving, and validating data needed by an organization about its human resources," personnel activities, and organizational unit characteristics.…”
Section: Hris Definitions and Rolementioning
confidence: 99%
“…HRIS have been seen as programmes that provide managers with information to make human resource decisions, monitor personnel activities and describe organisation unit characteristics (Kovach et al, 2002;Mathys and LaVan, 1982). Kovach and Cathcart (1999) noted that an HRIS need not be computerised since the main goal of information is to allow quicker decisions. The first forms of true HRIS were payroll systems created during the 1960s (Ball, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%